System dynamics modelling a practical approach - Coyle, R. G (Chapman & Hall, 1996)
With NATO's bombing campaign against Serbia now over, what strategic, long-range plans will the alliance employ to restore stability to the region? As the global economy continually changes in response to worldwide events, what investment strategies will firms implement to cope with changing markets? And how can major pharmaceutical companies solve the problem of having newly-developed products abandoned before they can even be launched on the market? This book is designed and written to give the applied statistician an insight into all these areas of investigation.